Curcumanes E and F, two rare sesquiterpenoids with a dicyclo[3.3.1]nonane moiety, from Curcuma longa and their vasorelaxant activities - Liu, Juan; Qiao, Ming-Ming; Peng, Cheng; Shu, Hong-Zhen; Meng, Chun-Wang; Liu, Fei; Xiong, Liang (Frontiers in Chemistry, 2022)
Two new sesquiterpenoids, curcumanes E (1) and F (2), were isolated from the rhizome of Curcuma longa, and their structures and absolute configurations were examined using extensive spectroscopic analyses and ECD calculations. Interestingly, compounds 1 and 2 are diastereoisomers possessing a rare sesquiterpenoid skeleton that has been reported only once before. Both curcumanes E and F exhibit significant vasorelaxant effects against KCl-induced contraction of rat aortic rings, with EC50 values of 5.10 ± 0.79 and 5.58 ± 1.77 μM, respectively. These findings enrich the data concerning this rare type of sesquiterpenoids and further indicate that these rare sesquiterpenoids can effectively reduce blood pressure.